Pulmonary hypertension with massive megalosplenia: A case report. Issue 12 (March 2019) - Yi, Tieci; Ma, Wei; Qiu, Jianxing; Ding, Wenhui
Abstract: Rationale: Pulmonary hypertension (PH) is a complicated disease which has complex causes and poor outcome. Many factors are involved in the increase of pulmonary artery pressure. It is often difficult to identify the specific cause of a particular patient. However, identifying the etiology is of great importance for specifying treatment strategies and improving the prognosis of patients. Patient concerns: A 58-year-old male was admitted because of fatigue, breath shortness for 6 months, which got worse in the last 3 months. The ultrasound cardiogram (UCG) indicated a remarkably elevated pulmonary artery systolic pressure (PASP = 82 mm Hg). He had hypertension for 15 years. Besides, his spleen was found to be enlarged since 15 years ago. Bone marrow biopsy of the patient revealed myeloproliferative neoplasm (MPN) with severe myelofibrosis (MF). Diagnosis: Myeloproliferative neoplasm (MPN) with severe myelofibrosis (MF) which in turn caused PH and portal vein hypertension (PVH). Interventions: We treated the patient with diuretics and fosinopril, and also steroids and thalidomide for his MPN/MF. Outcomes: Two weeks later, the pulmonary artery pressure (PAP) was remarkably decreased (PASP = 53.1 mm Hg by UCG, mean PAP = 21 mm Hg by right cardiac catheterization). Within 2 years' follow-up, his circulatory state and hematological state remained stable. Lessons: It is often difficult to define the cause of PH, but it is important for making the appropriate treatment at the same time.